A snapshot of pre- And Post-intervention changes among cardiovascular disease patients participating in the new Smoking Cessation Program - Azmi, Junainah; Nurumal, Mohd. Said; Nik Mohamed, Mohamad Haniki; Ab Rahman, Norny Syafinaz (Wolters Kluwer Medknow Publications, 2020)
Background: The study evaluates the changes of pre and post stages of behavioral change, motivation level, and smoking status among cardiovascular disease patients, participating in the new smoking cessation program in Hospital Tengku Ampuan Afzan, Kuantan.